Histomorphometric analysis of nuclear and cellular volumetric alterations in oral lichen planus, lichenoid lesions and normal oral mucosa using image analysis software - Sowmya S Venkatesiah; Alka D Kale; Seema R Hallikeremath; Vijayalakshmi S Kotrashetti (Indian Journal of Dental Research, 2013)
Introduction: Lichen planus is a chronic inflammatory mucocutaneous disease that clinically and histologically resembles lichenoid lesions, although the latter has a different etiology. Though criteria have been suggested for differentiating oral lichen planus from lichenoid lesions, confusion still prevails. Aims: To study the cellular and nuclear volumetric features in the epithelium of normal mucosa, lichen planus, and lichenoid lesions to determine variations if any. Materials and Methods: A retrospective study was done on 25 histologically diagnosed cases each of oral lichen planus, oral lichenoid lesions, and normal oral mucosa. Cellular and nuclear morphometric measurements were assessed on hematoxylin and eosin sections using image analysis software. Statistical Analysis: Analysis of variance test (ANOVA) and Tukey′s post-hoc test. Results: The basal cells of oral lichen planus showed a significant increase in the mean nuclear and cellular areas, and in nuclear volume; there was a significant decrease in the nuclear-cytoplasmic ratio as compared to normal mucosa. The suprabasal cells showed a significant increase in nuclear and cellular areas, nuclear diameter, and nuclear and cellular volumes as compared to normal mucosa. The basal cells of oral lichenoid lesions showed significant difference in the mean cellular area and the mean nuclear-cytoplasmic ratio as compared to normal mucosa, whereas the suprabasal cells differed significantly from normal mucosa in the mean nuclear area and the nuclear and cellular volumes. Conclusions: Morphometry can differentiate lesions of oral lichen planus and oral lichenoid lesions from normal oral mucosa. Thus, morphometry may serve to discriminate between normal and premalignant lichen planus and lichenoid lesions. These lesions might have a high risk for malignant transformation and may behave in a similar manner with respect to malignant transformation.